Weed response on fusel oil applied at initial and late post-emergence - Azania, C. A.M.; Azania, A. A.P.M.; Pizzo, I. V. [UNESP]; Schiavetto, A. R. [UNESP] (FapUNIFESP (SciELO), 2010)
This work aimed to study weed response to fusel oil rate applied at early and late post-emergence. The following species were studied at late and early post-emergence: Ipomoea hederifolia, Ipomoea quamoclit, Euphorbia heterophylla, Digitaria spp., Cenchrus echinatus and Panicum maximum. The experiment was arranged in a completely randomized design with six treatments and four replications. Fusel oil, an alcohol distillation byproduct, was applied at rates of 50, 125, 250, 375 and 500 L ha-1, plus control without application. The plots were constituted by polyethylene containers with 3 L capacity, filled with topsoil land from a fallow area. Visual symptoms of intoxication were verified at 7 and 30 days after application (DAA) and dry weight at 30 DAA. The variables were submitted to variance analysis according to the design,adjusting the data to obtain the dose-response curve by polynomial regression. The studied species were susceptible only to the application of 500 L ha-1 of fusel oil at early or late plant postemergence. The species Digitaria spp. was susceptible and E. heterophylla tolerant to fusel oil applied at early post-emergence, while the other species were moderately tolerant. E. heterophylla was susceptible, Digitaria spp., C. echinatus and P. maximum moderately tolerant and I. hederifolia and I. quamoclit tolerant to fusel oil applied at late post-emergence.
Resposta de plantas daninhas ao óleo fúsel aplicado em pós-emergência inicial e tardia
Keywords: By-product; Herbicide; Selectivity